Tháng Năm 28, 2023

Cho \(P = \frac{{\sqrt {x – 5\sqrt x + 6} }}{{\sqrt x – 2}}\)với \(x \ge 9\). Tính \({P^2}.\) A \(\sqrt {\frac{{\sqrt x – 3}}{{\sqrt x – 2}}} \) B \(\frac{{\sqrt x – 3}}{{\sqrt x – 2}}\) C \(\sqrt x – 2\) D \(\sqrt x + 3\)

Cho \(P = \frac{{\sqrt {x – 5\sqrt x + 6} }}{{\sqrt x – 2}}\)với \(x \ge 9\). Tính \({P^2}.\)

A \(\sqrt {\frac{{\sqrt x – 3}}{{\sqrt x – 2}}} \)

B \(\frac{{\sqrt x – 3}}{{\sqrt x – 2}}\)

C \(\sqrt x – 2\)

D \(\sqrt x + 3\)

Hướng dẫn Chọn đáp án là: B

Phương pháp giải:

– Phân tích \(x – 5\sqrt x + 6\) thành nhân tử

– Áp dụng \(\frac{{\sqrt A }}{{\sqrt B }} = \sqrt {\frac{A}{B}} \) với \(A \ge 0,B > 0\) để rút gọn biểu thức

– Tính \({P^2}\)

Lời giải chi tiết:

Điều kiện: \(x \ge 9.\)

\(\begin{array}{l}\frac{{\sqrt {x – 5\sqrt x + 6} }}{{\sqrt x – 2}} = \frac{{\sqrt {x – 2\sqrt x – 3\sqrt x + 6} }}{{\sqrt x – 2}}\\ = \frac{{\sqrt {\left( {\sqrt x – 2} \right)\left( {\sqrt x – 3} \right)} }}{{\sqrt x – 2}} = \frac{{\sqrt {\sqrt x – 2} .\sqrt {\sqrt x – 3} }}{{{{\left( {\sqrt {\sqrt x – 2} } \right)}^2}}}\\ = \frac{{\sqrt {\sqrt x – 3} }}{{\sqrt {\sqrt x – 2} }} = \sqrt {\frac{{\sqrt x – 3}}{{\sqrt x – 2}}} .\end{array}\)

\( \Rightarrow {P^2} = {\left( {\sqrt {\frac{{\sqrt x – 3}}{{\sqrt x – 2}}} } \right)^2} = \frac{{\sqrt x – 3}}{{\sqrt x – 2}}.\)

Chọn B.